Medication treatment and lifestyle for obesity: An integrative review (Research, Society and Development, 2025)
Obesity is a chronic non-communicable and multifactorial disease associated with the development of comorbidities. As it is one of the leading causes of death worldwide, it has great relevance for public health. Lifestyle and drug treatment are the main non-surgical alternatives for resolving this condition. This integrative review aimed to gather the main findings on drug treatment and lifestyle changes for obesity. The databases searched were PubMed, Web of Science, Scielo, and Lilacs in the past 5 years. For this, the PICOS methodology, the PRISMA protocol, and the Rayyan tool were used for study selection and inclusion. After reading the abstracts, full texts, and applying the inclusion and exclusion criteria, 6 studies remained for quantitative synthesis. It was noted that through self-monitoring of caloric intake and physical activity, cognitive-behavioral therapy (CBT) helps patients manage their goals and harmful behaviors, thus improving their eating and physical habits. Patients undergoing pharmacological treatment achieved overall physical and laboratory exam results similar to those who chose to change their lifestyle for the same purpose. Lifestyle changes, with nutritional and physical exercise instructions, CBT, and herbal pharmacological treatment are effective and safe, providing positive modifications, especially concerning the reduction of risks and consequences caused by obesity.